2002
DOI: 10.1063/1.1522819
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement and characterization of n+ superhalo implants in a 120 nm gate-length Si metal–oxide–semiconductor field-effect transistor using cross-sectional scanning capacitance microscopy

Abstract: Articles you may be interested inTwo-dimensional characterization of carrier concentration in metal-oxide-semiconductor field-effect transistors with the use of scanning tunneling microscopy Visualization of 0.1-μm-metal-oxide-semiconductor field-effect transistors by cross-sectional scanning tunneling microscopy Appl. Phys. Lett. 81, 2475 (2002); 10.1063/1.1509118Boron penetration in p-channel metal-oxide-semiconductor field-effect transistors enhanced by gate ionimplantation damage Two dimensional dopant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Scanning probe microscopy (SPM) is one of the most powerful surface analysis techniques. 3,4) Scanning capacitance microscopy (SCM) [5][6][7][8][9][10] and Kelvin-probe force microscopy (KFM) [11][12][13] are the two major operating modes of SPM for 2-D carrier/dopant distribution measurement. They are non-destructive techniques with high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning probe microscopy (SPM) is one of the most powerful surface analysis techniques. 3,4) Scanning capacitance microscopy (SCM) [5][6][7][8][9][10] and Kelvin-probe force microscopy (KFM) [11][12][13] are the two major operating modes of SPM for 2-D carrier/dopant distribution measurement. They are non-destructive techniques with high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies have been focused on optimizing the two-dimensional (2D) distribution of dopant ions around the channel regions. For this purpose, techniques of cross-sectional imaging of the device structures performed using scanning capacitance microscopy (SCM), [1,2] scanning spreading resistance microscopy (SSRM), [3,4] and electron holography [5] have been utilized for determining the 2D carrier distribution with nm-scale resolution. Although those techniques are capable of yielding high-spatial-resolution 2D carrier profiles around the S/D region from cross-sectional cuts of a MOSFET, measurement of the shallow channel, that is, the region just below the interface between the gate dielectrics and channel silicon, does not exhibit sufficiently good quality.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning capacitance microscopy (SCM), which uses a conductive microprobe to detect the tiny capacitance between probe tip and sample, has been widely used to profile the carriers of Si-based devices. [1,2] Also, it has been recently reported that SCM measurements are effective for inspecting the local electrical properties of polycrystalline materials. [3] We report the results of SCM measurements together with the energy dispersive x-ray spectroscopy (EDX) for n-type poly-Si (n-poly) layers and discuss the dopant distributions within the bulk grains and grain surfaces of n-poly.…”
Section: Introductionmentioning
confidence: 99%